Three chigger species (Trombidiformes: Trombiculidae) co-parasitizing a domestic cat in Brazil, including pathogen monitoring - Jacinavicius, Fernando de; Pereira Pesenato, Isabella; Takatsu, Julia Carvalho; Cousandier, Gabriela; Ochoa, Ronald; Welbourn, Cal; Barros-Battesti, Darci Moraes [UNESP] (Taylor & Francis, 2023)
The ecology of chigger mites has many unknown aspects, even with several recent studies addressing the taxonomy and systematics of this group. In Brazil, the chigger species recorded coparasitizing vertebrates include opossums in the Pernambuco State, lizards and rodents in the Piauí State, and rodents in the São Paulo State. Chiggers collected on a domestic cat, Felis catus Linnaeus, 1758 (Mammalia: Felidae), from Caxias do Sul, Rio Grande do Sul State, were sent to the Acarological Collection of Instituto Butantan (IBSP) to be identified. The species were identified as eight larvae of Eutrombicula tinami, two larvae of Parasecia valida Brennan, 1969, and two specimens of the genus Eutrombicula Ewing, 1938, which have been described here as Eutrombicula bassiniin. sp. Additionally, we amplified partial 18S rRNA gene sequences for E. tinami and E. bassiniin. sp. However, the attempts to amplify fragments of the gltA gene of Rickettsia were unsuccessful. The present study reports the coparasitism in a domesticated feline with these three species, the second record of E. tinami, the first record P. valida to the Rio Grande do Sul State, and the description of E. bassiniin. sp. http://www.zoobank.org/urn:lsid:zoobank.org:act:D0D6EEAB-DDB6-49F0-9651-4AFB96D4D588.
Keywords: Chigger mites; coparasitism; Felidae; South America; trombiculiasis